2021
DOI: 10.1093/arclin/acab062.105
|View full text |Cite
|
Sign up to set email alerts
|

A-87 Regional Cerebral Blood Flow in Self-Reported Somatic Anxiety

Abstract: Objective To identify regional cerebral blood flow (rCBF) differences between individuals who self-reported either low or high symptoms of somatic anxiety. Method Individuals who reported low levels of somatic anxiety (0-20th percentile;n = 8962,Mage = 39.2,39.2% female,62.6% Caucasian) and individuals who reported high levels of somatic anxiety (80-100th percentile;n = 6427,Mage = 40.9,39.0% female,69.5% Caucasian) were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, sedation was used especially in the young groups, which is believed to influence CBF quantification (Ogawa et al, 2015). Nonetheless, equivalent trajectories were demonstrated in other ASL studies, where ASC children elicited hypoperfusion (Mori et al, 2020;Saitovitch et al, 2019;Yerys et al, 2018), whereas the only study involving autistic adults displayed hyperperfusion (Peterson et al, 2019), thereby adding to the scarce and discrepant literature involving CBF in autistic adults, which displays both hyperperfusion (Pagani et al, 2012) and hypoperfusion (Mcdonald et al, 2020) compared to NA. However, additional studies are needed to verify the results on regional specificity considering the discrepancies found in different studies.…”
Section: Future Research Questions In Autism Researchmentioning
confidence: 89%
See 1 more Smart Citation
“…However, sedation was used especially in the young groups, which is believed to influence CBF quantification (Ogawa et al, 2015). Nonetheless, equivalent trajectories were demonstrated in other ASL studies, where ASC children elicited hypoperfusion (Mori et al, 2020;Saitovitch et al, 2019;Yerys et al, 2018), whereas the only study involving autistic adults displayed hyperperfusion (Peterson et al, 2019), thereby adding to the scarce and discrepant literature involving CBF in autistic adults, which displays both hyperperfusion (Pagani et al, 2012) and hypoperfusion (Mcdonald et al, 2020) compared to NA. However, additional studies are needed to verify the results on regional specificity considering the discrepancies found in different studies.…”
Section: Future Research Questions In Autism Researchmentioning
confidence: 89%
“…However, compatible results are present among the highest-powered studies, pointing to hypoperfusion in temporal, prefrontal, occipital, thalami, and basal ganglia in autistic children (Ohnishi et al, 2000; Starkstein et al, 2000). SPECT studies exclusively including ASC adults are scarce; however, one highly powered study including more than 140 participants demonstrated hypoperfusion in the basal ganglia and hyperperfusion in the cerebellum (Mcdonald et al, 2020). In summary, the majority of molecular imaging studies performed in autistic children demonstrated significant hypoperfusion, displaying a compliance between ASL and molecular imaging results (Bjørklund et al, 2018).…”
Section: Discussionmentioning
confidence: 99%